Exploring core functional microbiota responsible for the production of volatile flavour during the traditional brewing of Wuyi Hong Qu glutinous rice wine. (December 2018) - Huang, Zi-Rui; Hong, Jia-Li; Xu, Jia-Xin; Li, Lu; Guo, Wei-Ling; Pan, Yu-Yang; Chen, Shao-Jun; Bai, Wei-Dong; Rao, Ping-Fan; Ni, Li; Zhao, Li-Na; Liu, Bin; et al.
Abstract: The objective of this study was to explore the core functional microbiota for the production of volatile flavour during the traditional brewing of Wuyi Hong Qu glutinous rice wine, one of the most typical representatives of rice wine in China. Microbiological analysis based on high-throughput sequencing (HTS) technology demonstrated that bacteria of Lactobacillus, Bacillus, Leuconostoc, Lactococcus, Raoultella, Staphylococcus, Pediococcus, and Weissella, and fungi of Saccharomyces, Saccharomycopsis, Rhizopus, Monascus, Pichia, Wickerhamomyces, Candida, and Aspergillus were the predominant genera during the traditional fermentation process. Principal component analysis (PCA) based on the relative abundance showed that both of bacterial and fungal communities varied significantly in different fermentation phases. Some predominant microbial species or genera (including bacteria of Bacillus spp., Staphylococcus spp., Weissella spp., and P. acidilactici, and fungi of M. purpureus, R. oryzae, R. arrhizus var. arrhizus, and A. niger ) were detected at the initial brewing stage, and their populations decreased as the fermentation progressed, while those of Lactobacillus, Gluconacetobacter, Leuconostoc, Pichia, Wickerhamomyces, and Saccharomyces increased to become the predominant genera at the final stage. A total of 79 volatile compounds were identified in traditional fermentation starters and during the traditional brewing process, mainly including esters, alcohols, acids, aldehydes, ketones, and phenols. Heatmaps and PCA also revealed the significant variances in the composition of volatile compounds among different samples. Furthermore, the potential correlations between microbiota succession and volatile flavour dynamics were explored through bidirectional orthogonal partial least squares (O2PLS) based correlation analysis. Three bacterial genera, namely, Gluconacetobacter, Lactobacillus, Lactococcus, and three fungal genera of Pichia, Wickerhamomyces, and Saccharomyces, were determined as the core functional microbiota for production of main volatile compounds in Wuyi Hong Qu glutinous rice wine. To conclude, information provided by this study is valuable to the development of effective strategies for the selection of beneficial bacterial and fungal strains to improve the quality of Wuyi Hong Qu glutinous rice wine. Highlights: Wuyi Hong Qu glutinous rice wine is brewed with two traditional fermentation starters. Microbiota during traditional brewing were investigated by high-throughput sequencing. Correlations of volatile compounds and microbiota were preliminarily explored. Six genera were determined as core functional microbiota for production of volatile flavour.